2002
DOI: 10.1089/10507250252949450
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Changes After Levothyroxine Treatment in Subclinical Hypothyroidism

Abstract: In hypothyroidism, lack of thyroid hormones results in reduced cardiac function (cardiac output [CO]), and an increase of systemic vascular resistance (SVR). We speculated whether hemodynamic regulation in subjects with subclinical hypothyroidism (SH) (defined as mildly elevated thyrotropin [TSH] despite free thyroxine [T(4)] and triiodothyronine [T(3)] estimates within reference range) would benefit from levothyroxine (LT(4)) substitution. CO was measured by impedance cardiography, which is an observer indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 24 publications
4
42
0
1
Order By: Relevance
“…In this context, SH has been found to be associated with a deranged cardio-respiratory function, both at the level of anaerobic threshold and at peak exercise (23). Evidence suggesting systolic abnormalities in SH has recently been reported by other techniques such as ultrasonic myocardial textural analysis (24), impedance cardiography (25), and radionuclide ventriculography (26).…”
Section: Discussionmentioning
confidence: 97%
“…In this context, SH has been found to be associated with a deranged cardio-respiratory function, both at the level of anaerobic threshold and at peak exercise (23). Evidence suggesting systolic abnormalities in SH has recently been reported by other techniques such as ultrasonic myocardial textural analysis (24), impedance cardiography (25), and radionuclide ventriculography (26).…”
Section: Discussionmentioning
confidence: 97%
“…Faber et al 24 found a decrease in systemic vascular resistance and in the mean arterial pressure with LT-4 replacement among 16 women (mean age 60 years) with SH and mean serum TSH = 17.1 mU/l 24 . Nagasaki et al 25 also demonstrated that SH patients exhibited increased DBP, in a group of elderly patients (65.2 ± 2.6 years old), with lower serum HDL cholesterol levels 25 .…”
mentioning
confidence: 99%
“…Diastolic dysfunction both at rest and upon effort is the most consistent cardiac abnormality in patients with sHT, even in those with slightly elevated TSH levels (>6 mIU/L) (Arem et al, 1996;Biondi & Cooper, 2012;). Mild thyroid failure may also increase diastolic blood pressure as a result of increased systemic vascular resistances (Faber et al, 2002;Kahaly, 2000;Luboshitzky et al, 2002). Interestingly, restoration of euthyroidism by LT4 replacement is able to reduce systemic hypertension as well as improve left ventricular myocardial function (Brenta et al, 2003).…”
Section: Discussionmentioning
confidence: 99%